Which Donors, Which Funds? : The Choice of Multilateral Funds by Bilateral Donors at the World Bank - Reinsberg, Bernhard; Michaelowa, Katharina; Knack, Stephen (World Bank, Washington, DC, 2015)
The rapid growth of trust funds at multilateral development organizations has been widely neglected in the academic literature so far. Using a simple illustrative model, this paper examines the choice by sovereign donors among various trust fund options. The authors contend that the choice among the different trust funds involves a fundamental trade-off: larger funds provide donors with the benefit of burden sharing. Conversely, each donor can better assert its individual preferences in a fund with fewer other donors. The theoretical considerations yield testable implications on a range of factors affecting this fundamental tradeoff, most notably the area of intervention of the trust fund and competing domestic interests of donor countries. Using a sample of World Bank trust funds, the paper examines the participation decisions of Organisation for Economic Co-operation and Development/Development Assistance Committee donors over the past decade. In line with the theoretical argument, preference homogeneity among donors as well as indicators for global activities and fragile states assistance are robust determinants of participation in (large) multi-donor funds. In contrast, donors tend to prefer single-donor trust funds in areas in which their national interests dominate. Although they could use bilateral aid for the same purpose, they often prefer to channel their contributions through trust funds at multilateral agencies. Donors thereby reduce their own administrative costs, while benefiting from the expertise of the multilateral agency. These findings confirm prior qualitative case studies and evidence from donor reports, suggesting that reduced reliance on single-donor trust funds—a costly instrument from the perspective of multilateral agencies—can improve the development effectiveness of aid.